Women, Bibles, Ideologies - von Flotow, Luise (TTR, 2000)
AbstractWomen, Bibles, Ideologies - Julia Evelina Smith's Bible translation was undertaken in response to the religious fervour of the Millerites in 1840s USA. Published in 1876, in the highly politicized context of the women's suffrage movement, it influenced "The Woman's Bible" (1895). Yet its "literal" approach results in a text that is quite unlike a late 20th century "literal" version by Mary Phil Korsak from yet another ideological movement.